PERANCANGAN MOTION GRAPHIC CERITA RAKYAT ‘MANANGKABAU’ - Aulia Afif.Z; hendra afriwan (Universitas Negeri Padang, 2020)
The lack of attraction of folklore with minimum illustration presented in the textbook force the children around 13-23 years old to pick the audio visual. This situation makes the children does not like to read the book anymore. As easier for those children to remembered and understood the story if its visualize like comic and animation. In other words, the writer makes the motion graphic of Manangkabau folklore to attract those children attention in preserving the folklore and the society's norms. This motion graphic is hoping to present the moral message and visualize the story in more attractive ways.The design of motion graphic of folklore Manangkabau is using the 4-D design. The 4-D design is kind of the development of learning tools. This design is developed by S. Thiagarajan, Dorothy S, Semmel, and Melvyn I. Semmel (1974:5). This design consists of 4 parts, they are: 1. Definitive, 2. Design, 3. Development, and 4. Desiminate. The analysis of this design is using the descriptive qualitative and SWOT analysis approach (Strengths, Weaknesses, Opportunities, and Threats) in order to find the solution of the problem above.The main media of motion Manangkabau folklore graphic is designed in innovative and creative ways. Besides, This media is also supported by using the pin media, poster, social media (YouTube, Instagram), stickers, notebook and T-shirt, so that the messages consist in the story such as moral, educative and cultural values is fully delivered.Keyword: Motion Graphic, buffalo fight, folklore